Implementasi Audit Mutu Internal (AMI) sebagai Upaya Peningkatan Mutu Pendidikan di SMAN 1 Pulau Punjung - Rinny, Rinny; Jamilus, Jamilus; Rahmawati, Aulia (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Internal Quality Audit (AMI) is a key instrument in the education quality assurance system, serving to evaluate and continuously improve service quality. This study examines the implementation of AMI at SMA Negeri 1 Pulau Punjung, a leading high school in Dharmasraya Regency, using a qualitative case study approach. Data were collected through interviews, observations, and documentation, and analyzed using Kurt Lewin's Total Quality Management and change management theories. The results indicate that the implementation of AMI at this school has been effective, with the formation of an active audit team and follow-up actions based on audit findings. Challenges encountered include limited auditor competency, organizational cultural resistance, and the need to strengthen the use of information technology. AMI has had a positive impact on improving the quality of learning, infrastructure management, and school accreditation. Improvement strategies implemented follow the PDCA cycle, including teacher training, laboratory facility improvements, and the implementation of a digital-based reporting system. This study recommends strengthening auditor capacity, integrating AMI with TQM, and benchmarking with other leading schools to foster a sustainable quality culture in accordance with Islamic values that emphasize continuous evaluation and self-improvement